Scripted and unscripted aspects of creative work with knowledge - Bereiter, Carl; Cress, Ulrike; Fischer, Frank; Hakkarainen, Kai; Scardamalia, Marlene; Vogel, Freydis (International Society of the Learning Sciences, 2017)
Advances in scripting theory and advances in support for student-driven knowledge construction call for a reconsideration of long-standing issues of guidance, control, and agency. This symposium undertakes a fresh analysis based on the relations between two widely adopted approaches that may be poles apart but arguably viewed as variations within a common applied epistemological framework. The two approaches are scripted collaboration and Knowledge Building. Rather than focusing on similarities and differences, the symposium will address deeper problems such as reconciling external supports of all kinds with the self-organizing character of knowledge construction and integrating such supports into classrooms viewed as knowledge-creating communities. The centerpiece of the symposium is a panel discussion that includes experts who provide different theoretical viewpoints. In its synthesis the symposium will capture and make sense of what is strongest in the two approaches and provide a broad conceptual basis for next-generation initiatives.